Stable Probability Distributions and their Domains of Attraction - J.L. Geluk; Laurens F.M. de Haan (Tinbergen Institute, 1997)
The theory of stable probability distributions and their domains of attraction is derived in a direct way(avoiding the usual route via infinitely divisible distributions) using Fourier transforms. Regularly varyingfunctions play an important role in the exposition.
Keywords: 330; Wahrscheinlichkeitsrechnung; Theorie